OLYMPIC EDUCATION – Part 1. Theoretical and methodological principles of current Olympic education. - Galan, Y.; Beshlei, O.; Perederiy, V. (My University, 2021)
The Olympic Movement for its more than 120-year history is considered to be one of the most large-scale phenomenon today, which brings together the vast majority of the world. Consequently, the International Olympic Committee (IOC) as the governing body of the Olympic movement is one of the most influential international organizations. One of the main tasks of the IOC is to focus on encouragement and support of the initiatives aimed at integrating Olympic values in the life of society, but also promoting activities of the International Olympic Academy and other institutions that deal with the development of Olympic education. Ukraine is one of the leading countries in the promotion of the Olympic movement and Olympic education, which is recognized by international organizations. The most common forms include Olympic classes, small Olympic games, talks, quizzes, drawings competitions, meetings with champions and prize-winners of the Olympic ! teer movement and club work [139]. In addition, Ukraine has a network of Olympic education schools, which unites 276 educational institutions. The study of Olympic education in different years engaged domestic M.M. Bulatova, 2002 [28], O.M. Vatseba , V.P. Yukhimuk, 2004 [148], A.A. Tomenko, 2007 [123], V.M. Yermolova, 2010 [139], J.S. Sherbashin , 2009 [112], L.O. Radchenko, 2015 [99]) and foreign scientists (V.N. Sergeev, 2001 [108] , Georgiadis K., 2010 [45], Binder D., 2012 [11]). The ways of integrating Olympic education into the educational 6 process of school youth are thoroughly analysed in scientific and methodical sources [33, 76, 92, 112]. The studies also highlight the educational potential of the Olympic movement [29, 125, 111], outline the importance of integrating Olympic education when training professionals of physical culture and sports [14, 34]. The question of Olympic education as a positive factor that contributes to the humanization of society is reflected in the work of Ukrainian researchers: N.V. Moskalenko, V. Savchenko, 2007 [106] S.F. Matveev, Kohut I.A., Kropivnitskyi T.A., 2007 [73] Y. Timchak, 2010 [121], Ya.P. Galan, [44], M.M. Bulatov, 2008 [25] and others. A significant amount of research is devoted to the development of the content of Olympic education as a factor in the humanization of the physical culture of student youth. It is well known that in the implementation of Olympic education NOA has a leading role in ensuring the necessary physical activity, a high level of physical and moral development of the modern generation, the formation of a full-fledged personality. The variety of forms of Olympic education can ensure active involvement of children in regular exercise and sports, the development of their creative abilities, ethical and moral principles of personality, the formation of basic universal values, improving school performance, reducing morbidity and others. The results showed that the most common and used innovative forms of Olympic education are various intellectual quizzes, themed festivals, contests, quests, various research activities, themed games or events, Olympic lessons, etc. Each of these activities touches upon the main aspects of Olympism, promoting innovation through the variety of physical exercises that have an Olympic focus. All these factors have an indirect impact on increasing physical activity and the overall development of the younger generation.